2015
DOI: 10.1016/j.enggeo.2014.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Testing the application and limitation of stochastic simulations to predict the lithology of glacial and fluvial deposits in Central Glasgow, UK

Abstract: Glacigenic and fluvial deposits of variable lithological composition underlie many major cities in Europe and North America. Traditional geological mapping and 3D modelling techniques rarely capture this complexity as they use lithostratigraphic designations which are commonly based on genesis and age rather than lithological compositions.In urban areas, thousands of boreholes have been, and continue to be, drilled to facilitate the planning, design and construction of buildings and infrastructure. While these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(62 citation statements)
references
References 23 publications
0
62
0
Order By: Relevance
“…The proportion of (i) coarse grained (sand and gravel) and (ii) fine grained (silt and clay) deposits in each geological unit was calculated from lithological analysis of the large number of available borehole logs for central Glasgow (Turner et al 2014; Figure 4C). More detailed lithological analysis was done on data from the same borehole logs by Kearsey et al (2015), with comparable results.…”
Section: Results Of Investigations Intomentioning
confidence: 99%
See 1 more Smart Citation
“…The proportion of (i) coarse grained (sand and gravel) and (ii) fine grained (silt and clay) deposits in each geological unit was calculated from lithological analysis of the large number of available borehole logs for central Glasgow (Turner et al 2014; Figure 4C). More detailed lithological analysis was done on data from the same borehole logs by Kearsey et al (2015), with comparable results.…”
Section: Results Of Investigations Intomentioning
confidence: 99%
“…The most laterally extensive Quaternary deposit across Glasgow is glacial till of the Wilderness Till Formation, which crops out at the ground surface across much of the city (Figure 3), and rests on bedrock across much of the area (Kearsey et al 2015;Monaghan et al 2014). It is typically less than 5m thick, but can be thicker in drumlins, and becomes thinner and sometimes absent on higher ground ( Figure 3, Table 1) (Kearsey et al 2015, Monaghan et al 2014).…”
mentioning
confidence: 99%
“…These were rationalized to six dominant lithofacies (Clay, Diamicton, Organic deposits, Silt, Sand, Sand & Gravel) using the approach employed by Kearsey et al . (). The relative proportions of lithofacies were then calculated.…”
Section: Methodsmentioning
confidence: 97%
“…Initial processing of the data indicated that 147 different lithological descriptions have been used to describe the Quaternary sediments. These were rationalized to six dominant lithofacies (Clay, Diamicton, Organic deposits, Silt, Sand, Sand & Gravel) using the approach employed by Kearsey et al (2015). The relative proportions of lithofacies were then calculated.…”
Section: Calculating the Types Of Sediments That Filled The Featuresmentioning
confidence: 99%
“…It is likely that as additional high-quality data become available for the model domain, the performance of the subdivided model variograms will improve further, thus having an even greater impact on the 3D stratigraphic model accuracy and an improved basis for informing hydrogeologic parameter variability. Stochastic modelling approaches could also be applied within submodel zones to visualize and assess multiple model realizations and capture the variability in the model predictions (Kearsey et al 2015). The next step is to integrate this improved representation of the geologic spatial variability with hydrologic parameters to assess the effects on flow system conditions where water balance and hydraulic head distributions from field and model outputs can be evaluated.…”
Section: Rmse Resultsmentioning
confidence: 99%